2001
DOI: 10.5914/tropocean.v29i2.3032
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição de Moluscos Perfuradores de Madeira (Bivalvia-Teredinidae) no Estuário do Rio Manguaba, Japaratinga-Porto de Pedras, Estado de Alagoas de Acordo com a Salinidade.

Abstract: A distribuição espacial de moluscos bivalves perfuradores de madeira da família Teredinidae foi estudada na área estuarina do Rio Manguaba, importante manancial localizado no litoral norte do Estado de Alagoas. Para a área estuarina e de manguezal foram identificadas seis espécies Nausitora fusticula (Jeffreys, 1860), Neoteredo reynei (Bartschi, 1920), Bankia fimbriatula (Moll e Roch, 1931), Psiloteredo healdi (Bartschi, 1931), Teredo bartschi (Clapp, 1923) e Lyrodus floridanus (Bartschi, 1922) obtidas de cole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…According to Müller and Lana (2004), Neoteredo reynei is considered a tropical and subtropical amphi-Atlantic species with a preference for brackish waters and estuarine. A wide tolerance to salinity variation was also observed by Freitas and Mello (2001) and De-Carli and Manzi-Decarli (2012). Differently from the other observed species, specimens of Bankia gouldi were collected only at Site 1 (lower estuary), a region that receives more significant marine influence.…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…According to Müller and Lana (2004), Neoteredo reynei is considered a tropical and subtropical amphi-Atlantic species with a preference for brackish waters and estuarine. A wide tolerance to salinity variation was also observed by Freitas and Mello (2001) and De-Carli and Manzi-Decarli (2012). Differently from the other observed species, specimens of Bankia gouldi were collected only at Site 1 (lower estuary), a region that receives more significant marine influence.…”
Section: Discussionsupporting
confidence: 56%
“…In the present work, the species Nausitora fusticula was the most abundant, present mainly in the plots closer to the water, corroborating the results of Leonel et al (2002), who observed the occurrence of Nausitora fusticula in brackish waters, within a wide salinity gradient, strengthening the idea of adapting to salinity variation. Freitas and Mello (2001) reveal that the species Nausitora fusticula tolerates between 0.04 and 27 of salinity, occurring both in estuarine areas within the forest that are little flooded and on the margins of the mangrove covered by water during variation of tides and salinities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations